(untitled) (Journal of Medical & Health Sciences Review, 2026)
Background: Oral health is increasingly recognized as a critical component of overall well-being; however, in many low- and middle-income countries, it remains narrowly framed as a clinical issue, detached from broader social and development agendas. In Pakistan, particularly in resource-constrained settings, limited access to oral healthcare intersects with socioeconomic inequality, gender norms, and weak preventive systems, potentially undermining education, livelihoods, and social participation. Objectives: This study aimed to examine the linkages between oral health and key social development dimensions, explore community and stakeholder perceptions of oral health as a social development concern, and identify structural and institutional pathways through which oral health influences broader development outcomes among marginalized populations. Methods: A qualitative exploratory design was employed in rural and peri-urban communities of Khyber Pakhtunkhwa, Pakistan. Data were collected through semi-structured in-depth interviews and focus group discussions with 35 participants, including community members, healthcare providers, and local development stakeholders. Data were analyzed using thematic analysis, guided by social determinants of health and development frameworks. Results: Seven interrelated themes emerged. Poor oral health constrained educational participation through school absenteeism and reduced learning engagement; disrupted livelihoods by causing work absenteeism and income loss; and reinforced gendered inequities due to women’s limited autonomy and financial dependence. Social stigma associated with poor oral health reduced community participation and self-esteem. At the institutional level, oral health was largely excluded from development planning, with services focused on pain management rather than prevention. Oral diseases were widely normalized, delaying care-seeking. Despite these barriers, participants increasingly recognized oral health as integral to education, productivity, dignity, and long-term social development. Conclusion: Oral health in resource-constrained settings is deeply embedded within social, economic, and institutional structures, with far-reaching implications for development outcomes. Reframing oral health as a social development priority and integrating preventive, gender-responsive, and community-based approaches into development planning are essential for advancing equitable and sustainable health and development in Pakistan.